Social Citizenship for Older Persons? : Measuring the Social Quality of Social Pensions in the Global South and Explaining their Spread - Böger, Tobias; Leisering, Lutz (World Bank, Washington, DC, 2017)
Social pensions - non-contributory provisions for old age, mostly means-tested—have mushroomed in the global South since the 1990s, and have also been advocated by international organizations. Using the data base FLOORCASH constructed by the authors and their research team, they cover all countries of the global South, to go beyond existing case studies and selective comparisons. The authors investigate the contribution of social pensions to rights-based social protection and seek to explain their spread across the global South. While in Northern welfare states universal social services and social insurance are seen as the hallmarks of social citizenship as conceived by T.H. Marshall, measured by indices such as Esping-Andersen’s decommodification index, this paper advances a conceptualization of social rights that includes means-tested benefits, in order to recognize the bigger role of non-contributory transfers in developing countries. Applying a new measure of the social quality of social pensions, the authors detect considerable differences between countries, which are not reducible to the common distinction universal vs. means-tested benefits. Combing the social quality measure with the dimension of scale (population covered), the authors identify four normative models of old-age security. One of these models might herald a new social model for the South. Finally the paper applies event history analysis to explain the spread of social pensions across the global South, finding that standard domestic variables, subscription to international norms, and pension reform events were central drivers of social pension expansion.